IMC Preferences in BMC School Gresik - KARSTEN, Hadassah Elisha; WONO, Hilda Yunita; HERMAWAN, Jessica Nathalia (PT Keberlanjutan Strategis Indonesia, 2024)
In 2021, East Java Province, Indonesia, stood out as a leading provider of education services among the nation's 34 provinces. Private schools, predominant in East Java, surpassed their public counterparts, demonstrating early marketing efforts and innovation. BMC School, situated in Gresik Regency, known as the